NEW VARIETY OF WINTER GARLIC «STRELETS» - L. I. Gerasimova; V. V. Logunova; T. M. Seredin (Овощи России, 2016)
The article presents the results of breeding of new variety of winter garlic “Strelets” developed as a result of clonal selection from local sample acquired in the Altai Territory. The variety trial revealed high seed production of this cultivar. The cultivar is characterized by the big air bulbils and other valuable features.